Tinjauan Yuridis Perlindungan Hukum Terhadap Korporasi Atas Pembelian Tanah Girik di Hadapan Lurah dan Camat (Studi Kasus Putusan Nomor 18/Pdt.G/2023 Pengadilan Negeri Unaaha, Konawe) - Parhusip, Arif Timbul M; Nugroho, Meysita Arrum (PT Elaborium Elevasi Indonesia, 2025)
Bringing foreign investment into Indonesia, especially to build infrastructure for a production process such as a nickel smelter that processes soil mud (ore) into a nickel mineral material, certainly requires very large funding. Legal certainty is needed from the beginning of the investment process, namely determining the land area where the nickel smelter factory will be built. The land acquisition process is also very important, because on the land there will be activities worth hundreds of billions of rupiah to bring in materials, workmanship and preparations until checking/commissioning can be carried out and then declaring the facility ready for production. The government should protect investors with good faith in the process of procuring/purchasing land from the community. Legal protection is something that the state must provide to foreign parties who will bring large investments to Indonesia, which of course will create jobs for the Indonesian people, as well as a domino effect for economic growth along with the project, micro, small and medium economic actors will participate in the business activities of the foreign investors. The government is obliged to protect foreign investors from land mafia who always take advantage of every land sale and purchase activity for a development project so that later foreign investors will not get disturbances from the internal Indonesian community, either individuals or legal entities. Moreover, foreign capital investment is legally protected by the state as ordered by Law Number 25 year 2007 concerning Investment, which also includes legal protection for Foreign Direct Investment.